Examining the construct validity of burnout scale using confirmatory factor analysis - Ulfiani Rahman,; Wan Shahrazad Wan Sulaiman,; Rohany Nasir,; Fatimah Omar, (Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2015)
Many teachers find the demand of their job stressful to the extent that they show symptoms such as reduced performance, lack of attention towards the task, low commitment and low job satisfaction. The results of teacher stress can lead to burnout. This study was conducted to test the construct validity of the Burnout Scale. Therefore, the main objective of this study was to assess the goodness of fit of the measurement model of the Burnout Scale using confirmatory factor analysis (CFA). The Burnout Scale consists of three dimensions, namely emotional exhaustion, depersonalization, and reduced personal accomplishment. The study was conducted on 11 religious schools located in the North, East, South, Middle West of South Sulawesi, Indonesia comprising a total of 339 teachers who participated in the study. However, examination with the normality data showed that only 208 respondents were used as samples. The results of the study showed that the hypothesized measurement model of burnout did not show satisfactory goodness-of-fit of the model with the data, with the values obtained: χ2 = 656.986, CFI = 0.843, GFI = 0.828, TLI = 0.823, RMSEA = 0.080. The measurement model thus has to be revised. Results of the revised model showed a better fit, with χ2 = 115.400, CFI = 0.949, GFI = .931, TLI = 0.929, RMSEA = 0.060.